Assoggettamento e passioni nel pensiero politico di Judith Butler - Mastroberti, Chiara (Strumenti per la didattica e la ricerca, 2016)
Chiara Mastroberti retraces the most decisive moments of Judith Butler's work with the aim of deepening Butler's thoughts on the relationship between political subjection and individual passions. Rereading La vita psichica del potere and Parole che provocano (1997), passing through Vite precarie (2004) and Critica della violenza etica (2005), the author analyses Butler's discussion on fear, paranoia, melancholy and desire, framing it within the philosopher's broader ethical and political reflection. At the core of this reflection, there are the dialectics of "psychic life", oscillating between adherence and resistance to the social norm: passions are the key to reading this text in order to understand the origin and limit of the contemporary subject, its "passivity" and the secret of its survival.